−10y^9 ⋅ (?)=20y^15

11 answers

To solve for the missing factor, we need to divide both sides of the equation by -10y^9:

(20y^15) / (-10y^9) = -2y^6

Therefore, the missing factor is -2y^6:

-10y^9 * (-2y^6) = 20y^15
2y^2 ⋅ −3y
To multiply 2y^2 and -3y, we use the distributive property of multiplication:

2y^2 * -3y = 2 * -3 * y^2 * y
= -6y^3

Therefore, 2y^2 * -3y = -6y^3.
3y^5 ⋅ (?)=12y^15
To solve for the missing factor, we need to divide both sides of the equation by 3y^5:

12y^15 / 3y^5 = 4y^10

Therefore, the missing factor is 4y^10:

3y^5 * 4y^10 = 12y^15
−2y^9 ⋅ −4y^5
To multiply -2y^9 and -4y^5, we use the rules of exponents to multiply the coefficients and add the exponents of y:

-2y^9 * -4y^5 = 2 * 4 * y^9 * y^5
= 8y^14

Therefore, -2y^9 * -4y^5 = 8y^14.
−8y^3 ⋅ (?)=−56y^9
To solve for the missing factor, we need to divide both sides of the equation by -8y^3:

-56y^9 / -8y^3 = 7y^6

Therefore, the missing factor is 7y^6:

-8y^3 * 7y^6 = -56y^9
6y^5 ⋅ 3y
To multiply 6y^5 and 3y, we use the distributive property of multiplication:

6y^5 * 3y = 6 * 3 * y^5 * y
= 18y^6

Therefore, 6y^5 * 3y = 18y^6.